High pressure process treatment (HPP) as an alternative food preservation method on fruits and vegetables: A brief review / Suzihaque Maqsood-ul-Haque and Nur Aiedatul Shahirah Kamal - Maqsood-ul-Haque, Suzihaque; Kamal, Nur Aiedatul Shahirah (Universiti Teknologi MARA, 2021)
Highly processed and ready to eat food keep has been in high demand from the consumers from day to day. Thermal pasteurization can lead to undesirable sensory changes and there could be a high risk in ingesting pathogenic microbes from lack of proper pasteurization. High-pressure processing (HPP) could be a new alternative to preserve foods such as fruits, vegetables and fermented foods since it is less aggressive. The influence of HPP for the preservation of fruits, vegetables and fermented foods was proven to be effective towards the physicochemical properties of fruits and vegetables. The paper review in brief the effect of high-pressure process treatment as an alternative food preservation method. Observations were based on the physical and chemical properties such as color, texture and microbiological counts. This study demonstrated that the quality changes of foods can be preserve through HPP treatments.